Strategi Pemasaran Cicil Emas (CILEM) untuk Meningkatkan Minat Nasabah di BSI KCP Probolinggo - Nura Safira; Abd Aziz; Maula Nasrifah (Masyarakat Ekonomi Syariah Bogor, 2024)
Bank Syariah Indonesia (BSI) provides financing services for purchasing gold known as BSI gold installments. This product scheme is based on a murabahah contract as the basis of the agreement, with the use of a rahn (pawn) agreement as a collateral binder. The gold used is gold bullion, bullion and Antam precious metals, where the initial payment is 20%, while the remaining 80% can be paid in installments. This research aims to find out how the marketing strategy for gold installments affects people's interest in becoming gold installment customers at BSI KCP Probolinggo. This research method uses field studies and is descriptive qualitative in nature. The data collection techniques used included interview techniques, observation and documentation carried out with BSI KCP Probolinggo. The research results show that the Wa blast strategy of offering gold installments is the most effective strategy for existing customers, while the personal selling approach is the most effective strategy for attracting new customers at BSI KCP Probolinggo. With these two strategies, it is the best and most reducible strategy for long-term investment.